2022
DOI: 10.18240/ijo.2022.10.10
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis value of Chinese Ocular Fundus Diseases Society classification for proliferative diabetic retinopathy on postoperative visual acuity after pars plana vitrectomy in type 2 diabetes

Abstract: AIM: To compare the postoperative visual acuity among eyes with proliferative diabetic retinopathy (PDR) of different stages after pars plana vitrectomy (PPV) in type 2 diabetic patients. METHODS: A retrospective study was conducted for PDR eyes undergoing PPV in type 2 diabetic patients. All patients were divided into three groups based on Chinese Ocular Fundus Diseases Society (COFDS) classification for PDR: Group A (primary vitreous hemorrhage), Group B (primary fibrovascular proliferation) and Group C (pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Also, only ACD and ACV had a weak negative correlation with HbA1c levels. Similar to our results, other studies show no association between CCT and HbA1c levels [32,[51][52] . In addition, studies found that HbA1c levels do not affect curvature, CV, and corneal asphericity [33,35,53] .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Also, only ACD and ACV had a weak negative correlation with HbA1c levels. Similar to our results, other studies show no association between CCT and HbA1c levels [32,[51][52] . In addition, studies found that HbA1c levels do not affect curvature, CV, and corneal asphericity [33,35,53] .…”
Section: Resultssupporting
confidence: 92%
“…In agreement, Inoue et al [20] reported that in patients with type 2 DM the corneal endothelium is damaged, the density of endothelial cells decreases, and the coefficient of variation of the cell area increases, but CCT does not increase in them. Lin et al [32] in a hospital-based study reported that CCT was higher in diabetic subjects but this difference is not significant. In another study, 200 diabetic patients with 200 non-diabetic individuals were evaluated.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Consequently, conbercept has garnered widespread usage in the treatment of DR in China. At present, doctors tend to lean towards PPV as the preferred option for HR-PDR patients presenting with vitreous hemorrhage (VH) [16,[27][28] . Although PPV can preserve some degree of vision, it is accompanied by risks, being a procedure that is both invasive and costly.…”
Section: Introductionmentioning
confidence: 99%
“…The prognosis of patients with PDR can vary due to the extent of fibrovascular proliferation (FVP) in the fundus. PDR with severe FVP often leads to retinal detachment, while PDR patients with simple vitreous hemorrhage generally have a better prognosis than those with retinal detachment due to severe FVP ( 3 , 4 ). Moreover, young patients with PDR are more susceptible to severe FVP, resulting in a poorer visual prognosis ( 5 ).…”
Section: Introductionmentioning
confidence: 99%